Inpatient clinicians' approach to diagnosis of urinary tract infections in older adults using the COM-B model: a qualitative assessment - Sonali D. Advani; Nathan Boucher; Alison G.C. Smith; Connor Deri; Jillian E. Hayes; Rebekah Wrenn; Kenneth Schmader (Cambridge University Press, 2024)
Our interviews of inpatient clinicians (physicians, physician assistants) modeled after the Capability, Opportunity, and Motivation Model of Behavior model revealed opportunity and motivation as important drivers for overdiagnosis and overprescribing for asymptomatic bacteriuria in older adults. Understanding these barriers is an important step toward implementing age-friendly stewardship interventions.